0.6*(x-0.6)=12,解方程后并检验.

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/11 23:09:58
0.6*(x-0.6)=12,解方程后并检验.

0.6*(x-0.6)=12,解方程后并检验.
0.6*(x-0.6)=12,解方程后并检验.

0.6*(x-0.6)=12,解方程后并检验.
0.6*(x-0.6)=12
x-0.6=12÷0.6=20
x=20+0.6
x=20.6
验算
x=20.6
左边=0.6×(20.6-0.6)
=0.6×20
=12
等式成立
所以x=20.6是方程的解

0.6*(x-0.6)=12
x-0.6=20
x=20.6
0.6×(20.6-0.6)=0.6×20=12

0.6*(x-0.6)=12
x-0.6=12÷0.6
x-0.6=20
x=20+0.6
x=20.6
检验
0.6*(20.6-0.6)
=0.6*20
=12

解 0.6*(x-0.6)=12
x-0.6=12/0.6
x=20.6
检验
方程左边=0.6*(20.6-0.6)=0.6*20=12
方程右边=12
方程左边=方程右边
所以X=20.6是方程的解